Configuration of Ce‐doped LaNiO3 as an alternative to platinum‐free counter electrodes for dye‐sensitized solar cells. (2nd September 2022) - Gunasekaran, Ahalya; James, Sneha; Maridevaru, Madappa C; Aljafari, Belqasem; Anandan, Sambandam
Summary: The exorbitant cost, corrosive nature and rare abundance of Pt as counter electrodes has hampered the availability of dye‐sensitized solar cells (DSSCs). Perovskites, the complex metal oxides that have a diverse variety of oxidation states and high oxygen vacancy concentrations, have sparked a lot of interest in energy storage and conversion, with researchers focusing on alternative ideas for rate‐cut counter electrodes to magnify the cost‐cutting of DSSCs. Herein, instead of Pt, the three hydrothermally synthesized perovskites LaCeNiO3, LaNiO3, and CeNiO3 are employed as photocathodes for the fabrication of DSSCs. The electrochemical studies reveal that their electrocatalytic activity towards the iodine/iodide electrolyte is akin to a typical Pt photocathode. The electrons released by the perovskites by oxygen reduction reaction on its surface reduce the I3 − to I −, thus the regeneration of the dye to its ground state happens by collecting electrons from the I − ion redox mediator, and finally oxidation of I − to I3 − takes place. The LaCeNiO3 shows a higher short circuit current (13.75 mA cm −2 ) with a power conversion efficiency of 3.46%. It has 579 mV of open‐circuit voltage with a 0.37 fill factor value. The LaNiO3 shows lower values in comparison with LaCeNiO3 because the A‐site cation doping creates lattice deficiencies in LaCeNiO3 making it good for the iodine reduction reaction. Abstract : Perovskite nanostructures as an alternative Pt‐free counter electrode for dye‐sensitized solar cells